To study the effect of plant growth regulators and urea on flowering, fruiting and yield of custard apple (Annona squamosa L.) cv. Sindhan (Indian Journal of Arid Horticulture, 2025)
The experiment was laid out in Randomized Block Design (RBD) with three replications at Horticulture Instructional Farm, Department of Horticulture, C. P. College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Dist. Banaskantha, Gujarat during the year 2005 and 2006. The experiment involved fourteen treatments comprising of three levels each of NAA and GA, (50 ppm, 100 ppm and 150 ppm) alone and their combinations with 2% Urea, 2 % Urea alone and Control. Seventeen years old custard apple plants of uniform growth and size were selected. Plants were planted at distance of 6 m x 6 m. The experimental findings revealed the effectiveness of plant growth regulators and urea on flowering, fruiting and yield of custard apple as compared to control. The result indicated that the significantly minimum number of days was taken for flowering and fruit ripening were recorded with combined application of NAA 150 ppm + Urea 2% during both the years and in pooled data. The combined application of GA, 50 ppm + Urea 2 % treatment recorded significantly maximum hermaphrodite flower, more rate of fruit development, fruit size (7.31 cm and 7.75 cm), number of pickings of fruit (6.42), average number of fruits per tree (194.38), average fruit weight (216.93 g), fruit yield per tree (40.26 Kg), fruit yield per hectare (11182.49 Kg) and less number of rudimentary flowers during both the years and in pooled data.
Keywords: Custard apple; Plant Growth Regulators; flowering; fruiting